Design of Head Movement Controller System (HEMOCS) for Control Mobile Application through Head Pose Movement Detection - Tolle, Herman; Arai, Kohei (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Head movement has been found to be a natural way of interaction. It can be used as an alternative control method and provides accessibility for users when used in human computer interface solutions. The combination of Head-mounted displays (HMDs) with mobile devices, provide an innovation of new low cost of human-computer interaction. Such devices are hands-free systems. In this paper, we introduce a new method for recognizing head movement as the controller of mobile application and proposed a new control system using head movement only. The proposed method can determine specific head pose movement and respond it as a controller. The implementation of a music player application on an iOS devices shows that the proposed method is appropriate for a new experience of real-time human-computer interaction with head movement control only.